Cost Estimation System for Construction Project (CES-CP) - Upasana Narang; Firdaus Firdaus; Ahmad Rifai (ICON-CSE, 2014)
Bill of Quantity is a form used by the contractor to submit a price to the owner in order to obtain a construction contract.It takes the ability and experience to make bill of quantity, not everyone can do it. The development of “Cost Estimation System for Construction Project (CES-CP)” is aims to assist people to make Bill of Quantity. The development of this application use FAST (Framework for the Application of Systems Techniques) methodology. This application stored the knowledge that required to make Bill of Quantity. It can show which one of the Work Unit Price are recommended for use on Bill of Quantity and which ones are not. All Work Unit Data that used on Bill of Quantity of a project will be stored and can be displayed at any time as a reference. This application helps people to make Bill of Quantity and make the process of making Bill of Quantity becomes more efficient.